Platelet CD36 links overweight and a prothrombotic phenotype in patients with non-valvular atrial fibrillation - Wang, Hua; Yan, Wei-hong; Gong, Lei; Song, Nian-peng; Wang, Chun-xiao; Zhong, Lin (Frontiers in Cardiovascular Medicine, 2022)
Introduction The pathophysiological mechanisms linking the overweight and prothrombotic state of non-valvular atrial fibrillation (NVAF) are incompletely understood. Our objective was to evaluate the effect of platelet CD36 on the risk of stroke associated with overweight in NVAF patients. Methods A cross-sectional study enrolled 182 subjects with NVAF in two groups: normal weight (18.5 < body mass index(BMI) < 25.0 kg/m2) and overweight (BMI ≥ 25.0 kg/m2). Clinical data, medical history, vital signs, transthoracic echocardiography parameters, and medication were recorded. Biochemical characteristics including blood glucose and serum lipid were analyzed in the Laboratory. Results The expression of platelet CD36 and integrin αIIbβ3 was detected by flow cytometry. Among the 182 patients with NVAF, 68 (37.36%) were classified as normal weight, 114 (62.64%) as overweight. With an increase in BMI, waist-hip ratio, cholesterol, triglycerides, left atrium diameters, and the ratio of mitral inflow E velocity to myocardial e' velocity in the mitral annulus (E/e') increased significantly (P < 0.05). The mean fluorescent intensity of platelet CD36 increased significantly in overweight patients (P < 0.01), in line with platelet activation biomarkers (platelet integrin αIIbβ3). Platelet CD36 was positively correlated with BMI and platelet integrin αIIbβ3, respectively (P < 0.05). Additionally, platelet CD36 and BMI were independent risk factors for platelet activation in patients with NVAF. Conclusions Platelet CD36 is speculated to mediate the complex crosstalk between overweight and platelet hyperactivity, leading to the prothrombotic state in overweight patients with NVAF. Platelet CD36 could be a potential target for preventing the prothrombotic state in overweight patients with NVAF.